If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 15 = 2x + 75 Reorder the terms: 15 + 5x = 2x + 75 Reorder the terms: 15 + 5x = 75 + 2x Solving 15 + 5x = 75 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 5x + -2x = 75 + 2x + -2x Combine like terms: 5x + -2x = 3x 15 + 3x = 75 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + 3x = 75 + 0 15 + 3x = 75 Add '-15' to each side of the equation. 15 + -15 + 3x = 75 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = 75 + -15 3x = 75 + -15 Combine like terms: 75 + -15 = 60 3x = 60 Divide each side by '3'. x = 20 Simplifying x = 20
| 8x(3x-3)= | | 8a-5=35+6(a-5) | | 2.5x+1.8=6.7 | | 1/2y=-2.3 | | y=-0.5(x-10)(x+14) | | x^2-4x=22 | | y=x-4/5 | | 4.28-0.54x=5x-2.645 | | 20=-4(4x-5) | | x/0.b=7.2 | | 5(n-3)=-20 | | 20c^2-17cr-63r^2= | | 2(-2n-7)=6(n+1) | | .50(-4+6x)=.33x+.66x+5.94 | | 7(x+2)=13x-7 | | 8(5y+3)=5y-5 | | 0+5=x | | 49-(2x+15)=2(x+7)+x | | 50=20n | | -4x+11=-5 | | a^2-8a+1=0 | | -20t^4+48t^3+5t^2= | | 6-6(3x-3)=-12 | | e^7/10x=4 | | 0.2(c-3)=-11 | | -8(4n-5)= | | (x-1+2i)(x+1-2i)=0 | | 100x^(1/2)-2x=625 | | 5x-4=-4x+32 | | 9a+5b=18 | | 135=67+j | | 77=e+28 |